Review of “Alfred Hitchcock’s Psycho Live Orchestra” (2023) (Sound Stage Screen, 2023)
Review of “Alfred Hitchcock’s Psycho Live Orchestra” (Milan, Fondazione Cariplo Auditorium, March 11, 2023). Orchestra Sinfonica Giovanile di Milano conducted by Anthony Gabriele.